Corneal aberrations in keratoconic eyes: influence of pupil size and centering - Comastri, Silvia Ana Elva (2011)
Ocular aberrations vary among subjects and under different conditions and are commonly analyzed expanding the wavefront aberration function in Zernike polynomials. In previous articles, explicit analytical formulas to transform Zernike coefficients of up to 7th order corresponding to an original pupil into those related to a contracted displaced new pupil are obtained. In the present paper these formulas are applied to 20 keratoconic corneas of varying severity. Employing the SN CT1000 topographer, aberrations of the anterior corneal surface for a pupil of semi-diameter 3 mm centered on the keratometric axis are evaluated, the relation between the higher-order root mean square wavefront error and the index KISA% characterizing keratoconus is studied and the size and centering of the ocular photopic natural pupil are determined. Using these data and the transformation formulas, new coefficients associated to the photopic pupil size are computed and their variation when coordinates origin is shifted from the keratometric axis to the ocular pupil centre is analyzed.